Efficiency of Polyethylene Terephthalate Glycol Thermoplastic Material to Functional and Expansion Forces in Orthodontic Applications: An Experimental Study - Anosh A. Haik; Yassir A. Yassir (The Scientific World Journal)
Conclusions: The MTB can withstand both required expansion and functional load without deformation.